HISTORY OF RUSSIAN FOLK DANCES - Nukisbay Abdiramanov (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article discusses the origin, history, formation and development of ancient Russian folk dances. It is said that the history of Russian folk dance was formed in connection with the ancient traditions and religious ceremonies of the local people.